Konsep Uswatun Hasanah dalam menghadapi Fenomena Hoax - Megawati Megawati (CV. Syntax Corporation Indonesia, 2022)
The hoax phenomenon that occurs in the midst of society is very worrying. Because it can divide the nation. It is as if the hoax was made to benefit one side by bringing down the other. This is certainly not the right way to do politics. Finally, honesty in politics is very rare nowadays. This study aims to analyze the concept of uswatun hasanah in dealing with the hoax phenomenon in the current era. This research was conducted using a qualitative descriptive method. Descriptive research is a research method that seeks to describe and interpret objects as they are. The form of research used is qualitative research, namely research that understands social phenomena in natural conditions. if the concept of Uswatun hasanah is always applied in everyday life, then gradually it can become the character of Indonesian society. If every Muslim applies this concept, the circulation of hoaxes that are so widespread will begin to be minimized. And Islam has taught that in conveying news according to the instructions and the right way and hoax news can be solved by using Tabayyun.